Aging and the Pandemic Care Triangle: A View from a Barcelona - Ribas-Mateos Natalia; Herrera Encarna (Journal of Aging Research And Healthcare, 2023)
This triangle of care is the result of an ethnographic research conducted with hard pandemic restrictions in Barcelona during 2020. Even if it is based in a bibliography on gender and migration, care and aging, the article is basically empirical. For the interpretation of the debates and discussion groups carried out, we identify here: the elderly person (as we have seen in the interviews in the previous article, Natalia-Ribas Mateos and Herrera 15,“The care debate during the first covid lockout in Barcelona); the caregivers - from family members to hired workers, especially immigrant women- and thirdly, as the third aspect of the triangle, and which remains in this article more blurred, from municipal and health public services. The pandemic highlights the existing systemic inequalities, particularly affecting the elderly, but also migrants and ethnic minorities, people who work in the care sector, and health personnel.
Keywords: Triangle of care